Morphology and phylogeny of two new ciliates, Sterkiella sinica sp. nov. and Rubrioxytricha tsinlingensis sp. nov. (Protozoa, Ciliophora, Hypotrichia) from north-west China. Issue 2 (4th March 2017) - Chen, Lingyun; Zhao, Xiaolu; Shao, Chen; Miao, Miao; Clamp, John C.
Abstract : Two new hypotrichous ciliates, Sterkiella sinica sp. nov. and Rubrioxytricha tsinlingensis sp. nov., were isolated from two different locations in China (the former from the upper 10 cm of soil in the Sangke Grassland, southern Gansu Province and the latter from a freshwater pond in the northern part of the Tsinling Mountains, south-western Shaanxi Province). We describe their morphology, infraciliature, and molecular phylogeny. Compared with its congeners, S . sinica sp. nov. is characterized by an elongate oval to elliptical shape with the anterior end narrowly rounded and the posterior end broadly rounded, consistently 18 frontoventral transverse cirri, cirrus III/2 farther toward the anterior than cirrus IV/3 and closer to cirrus IV/3 than to paroral, cirrus V/3 closer to cirrus V/4 than cirrus V/2, cirrus V/2 closer to cirrus VI/2 than cirrus V/3, three caudal cirri narrowly separated and not elongated, and terrestrial habitat. Compared with its congeners, R . tsinlingensis sp. nov. is characterized by a length in vivo of 100–180 μm, yellow-brown in colour, two macronuclear nodules and two or three micronuclei, yellow-green cortical granules, marginal rows almost confluent posteriorly, six dorsal kineties and three caudal cirri, caudal cirri and dorsal bristles almost indistinguishable when viewed in vivo, and freshwater habitat. Phylogenetic analyses based on small-subunit rRNA sequences revealed S . sinica sp. nov. associates most closely with Sterkiella sp. JS-2012d although the genus Sterkiella is not monophyletic. Rubrioxytricha tsinlingensis sp. nov. and R . ferruginea cluster together within a clade that also includes R . haematoplasma, Ponturostyla enigmatica and Pseudocyrtohymena koreana . http://www.zoobank.org/urn:lsid:zoobank.org:pub:27060A1C-F0D4-4FB2-866A-66F939B12105